Maltrato fisico y su incidencia en el trastorno de estrés post traumatico en una adolescente de 15 años de edad del cantón Vinces - Navarro Higuera, Carolina Elizabeth (2021)
Post-traumatic stress disorder is a disorder that is characterized by being produced by the exposure of a traumatic event, this event can be of a physical, emotional or behavioral nature, which generated a great impact at the mental level in the patient, thus producing the disorder; Symptoms in post-traumatic stress disorder can appear immediately or up to two years after exposure of the event, a characteristic symptomatology is the presence of flashbacks, which are memories of the traumatic event. Although there are different precipitating events that evoke the disorder, this case study focused on physical abuse, this being any voluntary action that causes or may cause injuries, despite the fact that domestic violence is very common, therefore it has been normalized and subtracted Importance, this event of violence is a great trigger for the disorder, being an event of great impact for the person and having a great burden of physical affectation that in turn leads to cognitive, behavioral, emotional and somatic areas thus generating the disorder.